Pensare per immagini nella società connettiva e collettiva - Porcheddu, Federica (Scenari, 2024)
This essay explores the transformation of the individual and society in the information age through the work of the anthropologists Pierre Lévy and Derrick De Kerckhove. Lévy highlights the role of images as triggers for interaction and communication, while De Kerckhove extends this view to connectivity, emphasising the importance of digital networks in the dissemination and generation of knowledge. The work aims to reinterpret the innovative ideas of Walter Benjamin and Aby Warburg in order to decipher today’s society, with a focus on the influence of images in the social and cultural context. The essay thus aims to investigate these issues of fundamental importance for contemporary society.